Peasant strategies for the consolidation of family agriculture in Los Altos de Chiapas, Mexico - Gómez Martínez, Emanuel (2019)
Has productive diversification allowed the peasant families of Los Altos de Chiapas to consolidate their strategies of social reproduction? To answer this question, this article characterizes peasant family agriculture to understand its level of economic consolidation. The research methodology is a case study on a regional and local scale, including a statistical review to characterize the problem, conducting a survey in two municipalities in the region, participatory observation of traditional agriculture work in demonstration plots of native corn improvement, monitoring of organic production processes of vegetables, honey and coffee. The result is a profile of the regional agricultural economy that allows the analysis of productive diversification strategies, highlighting the processes of agroecological management of corn, coffee and honey. The study allows us to discuss the typology of Peasant Family Agriculture (CFA) proposed by FAO to characterize the level of consolidation of peasant family agriculture. The conclusions allow us to understand in what process of economic consolidation the peasant strategies are found. The study offers guidelines to improve the processes of organization of the peasant family economy.